The Implementation of Microworld Logo in Classrooms - Setyaningrum, Wahyu (PYTHAGORAS Jurnal Matematika dan Pendidikan Matematika, 2008)
The idea of Microworld Logo brought new perspectives in education. It gives inspiration to develop and look deeply into the powerful ways in which computers and educational software might improve teaching-learning processes. However, the implementation of this Logo seems to be unsuccessful. This paper discusses and evaluates the implementation of Logo in classrooms' context and discusses some obstacles in its implementation in classrooms so that teachers could get lesson from that. It considers the notion of Logo's history and its preceding implementation to identify the problems on Logo's implementation. This study shows that the failure of Logo implementation might be comes from the limitations of Logo itself, human and technical resources, and learning environments that are related with curriculum and schools policies.